Single centre experience in 1202 biological prosthesis: a comparison between sutured, sutureless and surgical transcatheter aortic valve. (14th October 2021) - Mariani, C; Murana, G; Botta, L; Gliozzi, G; Folesani, G; Santamaria, V; Tassi, S; Di Marco, L; Pacini, D
Abstract: Background/Introduction: Different types of bio-prosthesis are now available for the treatment of aortic valve disease. In absence of the "ideal" heart valve prosthesis, the best choice may be customized on the basis of the patient's profile. Purpose: The aim of this study was to compare results in different subgroups of bio-prosthesis in elderly patients (>75 years old) undergoing conventional or surgical trans-catheter aortic valve replacement (AVR). Primary outcome was all cause mortality, secondary outcomes were: early post-operative complications (stroke, AV-block, acute kidney injury requiring temporary dialysis), freedom from structural vascular disease (SVD) and from re-operation. Methods: In this retrospective study we analysed 1202 patients over 75 years old, underwent AVR from 2002 to 2018. Inclusion criteria were: age >75 years underwent AVR; we divided our population in 3 groups according to different strategy: primary aortic valve replacement with sutured (group 1, n=1005), sutureless (group 2, n=103) or surgical trans-catheter aortic valve replacement (group 3, n=94). Exclusion criteria: concomitant cardiac procedure other than coronary artery by-pass graft (CABG) or endocarditis. Patient and disease characteristics are described as numbers and percentages, continuous data were expressed using mean and standard deviation. Differences between groups were evaluated using either Student t-test or Mann-Whitney U test or ANOVA test. Survival curves of the primary outcome and freedom from secondary outcomes were built with the Kaplan-Meier method. Results: The mean age of the overall population was 80.5±3.6 years with a mean STS score of assessed at 2.79±2.2% (2.27±1.0 for standard AVR, 3.3±2.2% for sutureless and 6.4±4.5 for S-TAVR, p-value<0.001). Early outcomes are depicted in figure 1. The overall 30-day mortality was 2.9%; among the different groups we observed 2.3%, 4.9% and 7.2% for sutured, sutureless and surgical-TAVR, respectively (p-value=0.01). The groups statistically differed also for permanent pacemaker implantation (sutured AVR 2.2%, sutureless AVR 4.9%, TAVR 9.6% (p-value<0.001) and acute renal failure requiring temporary dialysis sutured AVR 3%, Sutureless AVR 1.9% and Surgical TAVR 9.6% (p-value=0.004). The survival rate at follow-up was significantly different among group (log-rank <0.001, figure 2). Instead, freedom from reoperation was similar between cohorts (figure 2.) Conclusion(s): The outcomes of surgical AVR in a elderly population could be safely guaranteed with different biological prosthesis and operative techniques. A patient tailored approach should be always advised to improve current available transcatheter options. Funding Acknowledgement: Type of funding sources: None.